User experience analysis of Peduli Lindungi-applications using heart metrics in Eid Al-Fitr travellers - Fannya, Puteri; Happy Putra, Daniel; Aula Rumana, Nanda (International Journal Of Community Medicine And Public Health, 2023)
Background: As implementation of COVID-19 surveillance, the government has created a mobile application "Peduli Lindungi" which functions as tracing, tracking, warning and fencing in the Republic of Indonesia. The purpose of this study is to describe the user experience of the Peduli Lindungi application using heart metrics for Eid Al-Fitr travellers. Methods: This research was a quantitative study using a cross sectional design. The variables that will be seen as a description of the user experience are happiness, engagement, adoption, retention, task success. The number of samples in this study were 102 respondents. The research was conducted on travellers from the Jakarta, Bogor, Depok, Tangerang and Bekasi areas. Results: The result of this study found that the score of the happiness variable was 71.37%, engagement was 74%, adoption was 74.71%, retention was 70.39%, task success was 80.14%. Based on the level of conformity of goals and the performance of the Peduli Lindungi application, out of 27 statement items assessed by respondents, only 7 items had a value ≥0. This means that only about 25.92% of the items meet the expectations of the users. Items that meet user expectations are engagement, adoption, and task success variables. Based on the goals that have been set, only the task success variable meets the target user, 80% of the community has succeeded in using the features in the Peduli Lindungi application. Conclusions: The features, appearance and functions of the Peduli Lindungi application must be improved so that users can feel comfortable whenever they use it.